DIFFERENTIATION OF RUNNERS ATHLETES IN THE METABOLIC ADAPTATION TO THE BRUCE ERGOSPIROMETRY TEST: AN APPROACH BY DRIFTS CONSIDERING GENDER (Fiep Bulletin - online, 2013)
In the present study 34 runners (12 in 2008, 14 in 2009 and 8 in 2010) from the UNISC Athletics Team were evaluated by anthropometry and ergospirometry associated with Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS) of whole blood for differentiation of blood adaptation patterns with regard to gender. The athletes underwent the Bruce Protocol Treadmill Test, using gas analyzer and evaluating heart rate, maximum oxygen consumption (VO2max), maximum carbon dioxide production (CO2max) and respiratory quotient (RQ) at rest (pre-test) and every 20 seconds up to 3 minutes after the end of the test (exhaustion or termination of the protocol). The evaluation of blood pressure was performed at rest, every 3 min protocol (transition between stages) and after recovery. The blood collection by brachial venipuncture was performed in the pre-test and 10 minutes after the termination of protocol (pos-test) and blood samples were analyzed by DRIFTS through the full spectrum. It was observed significant differences between male and female athletes in the pre-test stage in the three years of collection. Significant differences were also found between the genders in the post-test stage in the three years, and in 2009 the spectral ranges that presented significant differences were larger. It is possible to conclude that the FT-IR of whole blood may be used to find differences between genders in the adaption of athletes during the Bruce Ergospirometry Test.
Keywords: athletes; DRIFTS; metabolic adaption